BIO621: Integrative Physiology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2018)
This course is designed to provide students with an overview of the broader aspects of physiology that involve the integration knowledge from such life-science disciplines as anatomy, biochemistry, mathematics, physics and, physiology. The course will also show how biophysics has so far contributed to a better understanding of neurobiology. Emphasis will be on the vertebrate, particularly mammalian nervous system. Students participation in class discussion and in-class assignments, as well as time spent on the homework assignments will be critical components of the learning process.